An evaluation of inter-organisational information systems development on business partnership relations - Elizabeth A. Williamson (International Journal of Business Science & Applied Management (IJBSAM), 2007)
Inter-organisational information systems (IOS) are being used within SCM to improve businesses processes and to facilitate closer working relations with business partners. However, the technologies themselves impact on this relationship as they allow various levels of information flows, communications, function integration and partner integration. The aim of this paper is to evaluate IOS development influencing partnership integration within Supply Chain Management (SCM) by investigating thirteen businesses that use a variety of IOS. IOS are classified into Elementary IOS, Intermediate IOS and Advanced IOS. Organisational variables such as information flows, partner co-ordination and integration, partner trust and confidence are measured against the level of IOS development. Variables such as management commitment, financial costs, system standards and partner resistance are investigated as forces or barriers, and related to different levels of IOS development. This research concludes that IOS development results in increased information flows and coordination which supports the development of trust and confidence in business partners. However, the customer position in the supply chain, whether it be retailer, distributor or manufacturer can influence the use of IOS of its business partners. Also, although IOS allows businesses to source and contact a larger range of business partners, the tendency is for businesses to use a smaller number of partners. This work also shows that IOS development changes a business's relationship with its partners and moves it towards partnership integration. However, a number of organisational factors impact on this integration. These factors vary with the level of IOS development. Management commitment and showing the requirement for IOS development can act as a positive force in developing IOS or as a barrier against IOS development. Other barriers include resistance from business partners, financial costs, lack of system standards and technical maturity of the companies. The effect of these barriers also is affected by the level of IOS development.
Keywords: 650; inter-organisational information systems; supply chain management; business partnership relations